Zbtb38 is a novel target for spinal cord injury - Cai, Yafei (Oncotarget, 2017)
Spinal cord injury (SCI) is currently incurable since treatments applied to clinic are limited to minimizing secondary complications and the mechanisms of injury-induced spinal cord damage are poorly understood. Zbtb38, also called CIBZ, is highly expressed in spinal cord and it functions as a negative regulator in SCI-induced apoptosis. We show here that Zbtb38 is downregulated under endoplasmic reticulum (ER) stress, which promotes ER stress-associated apoptosis in human bone marrow neuroblastoma cells. In the traumatic SCI mice, ER stress presented in injured spinal cord induced repression of Zbtb38 expression and triggered Zbtb38-mediated apoptosis. ChIP-QPCR analysis revealed that ATF4, an ER-stress inducible transcription factor, directly activated Zbtb38 transcription by binding to the Zbtb38 promoter. However, this binding was significantly reduced following SCI, leading to a sharp decrease in Zbtb38 expression. Restoring Zbtb38 function in injured spinal cord by injection of lentivirus containing Zbtb38 into SCI mice, significantly alleviated secondary damage of spinal cord with decreased ER stress-associated apoptosis and partially recovered spinal cord functions. These findings demonstrate that restoration of Zbtb38 expression can reduce secondary tissue damage after SCI, and suggest that a therapeutic strategy for targeting Zbtb38 may promote functional recovery of spinal cord for patients with SCI.